2014
DOI: 10.3389/fnmol.2014.00063
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin pathways in neurodegenerative disease

Abstract: Control of proper protein synthesis, function, and turnover is essential for the health of all cells. In neurons these demands take on the additional importance of supporting and regulating the highly dynamic connections between neurons that are necessary for cognitive function, learning, and memory. Regulating multiple unique synaptic protein environments within a single neuron while maintaining cell health requires the highly regulated processes of ubiquitination and degradation of ubiquitinated proteins thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 217 publications
1
106
0
2
Order By: Relevance
“…This comes as no surprise, as glutamate can induce an endoplasmic reticulum stress-associated death signalling cascade in neuronal cells [28] resembling the unfolded protein response known to promote a global transcriptional reprogramming [29]. The particular finding also supports the speculation that the observed up-regulation in protein levels of these chaperones is caused probably by post-translational modifications known to block protein turnover and promote protein stability, such as ubiquitination [30], which needs further investigation.…”
Section: Discussionsupporting
confidence: 54%
“…This comes as no surprise, as glutamate can induce an endoplasmic reticulum stress-associated death signalling cascade in neuronal cells [28] resembling the unfolded protein response known to promote a global transcriptional reprogramming [29]. The particular finding also supports the speculation that the observed up-regulation in protein levels of these chaperones is caused probably by post-translational modifications known to block protein turnover and promote protein stability, such as ubiquitination [30], which needs further investigation.…”
Section: Discussionsupporting
confidence: 54%
“…It is an E3 ubiquitin ligase protein, which interacts with HSC70-HSP70 and HSP90 and helps substrate ubiquitination and degradation of misfolded protein by the proteasome system [73]. CHIP serves as a link between the folding-refolding machinery in proteasome degradation pathways and has a direct role in a particular protein quality control pathway [74].…”
Section: Although the Mechanistic Details Of Neuroprotection By Cur Imentioning
confidence: 99%
“…Several studies on AD have shown that various proteins are subjected to modifications such as phosphorylation, ubiquitination, and more recently, SUMOylation [24][25][26][27][28].…”
Section: Sumoylation In Admentioning
confidence: 99%